Scattering of partially coherent surface plasmon polariton fields by metallic nanostripe - Salman Daniel; Kimmo Saastamoinen; Sergey A. Ponomarenko; Ari T. Friberg (Journal of the European Optical Society-Rapid Publications, 2019)
Abstract Background Surface plasmon polaritons (SPPs) are electromagnetic waves that propagate at a metal-dielectric interface. Until recently, monochromatic, fully coherent SPPs have mainly been considered. Methods We investigate by numerical simulations the generation and properties of polychromatic, partially coherent SPPs and their scattering from a nanostripe. We use both in-house and commercial codes. Results A standing SPP field is created in Kretschmann’s setup between the excitation point and the nanostripe. From the scattered far-field spectrum, all spatiotemporal coherence properties of the SPP field pattern can be deduced. Illustrative examples of such coherence variations are analyzed. Conclusions Plasmonic nanostructures produce strong confined SPP fields of widely controllable coherence.